Turkey : Higher Education Policy Study, Volume 1. Strategic Directions for Higher Education in Turkey - World Bank (Washington, DC, 2012)
Countries that invest heavily and effectively in education and skills to produce information and knowledge will benefit economically and socially. The European Union (EU) has set the goal to make Europe the most competitive and dynamic knowledge-based economy in the world. Turkey, in its Ninth Development Plan, aims to increase educational attainment and develop a lifelong education strategy to meet the requirements of a changing and developing economy and labor market. To meet the EU goal and the Turkey goal requires education systems that are more flexible, more effective and more easily accessible to a wider range of people. Education and skill levels in Turkey lag behind international standards, including the European Union. As highlighted in figures and discussion in a later section of the paper on access and equity, results of international tests show poor performance for many students in Turkey and participation in secondary education, as well as tertiary education, is low by international standards. Significant disparities also exist in educational quality and access by gender, social and economic group, and geographic location.